Exosomes from liver progenitor cells carrying JAG1 activate notch signaling to promote liver regeneration in PVL rats - Mingqi Liu; Yan Zhu; Zhishuai Li; Yong Yu; Duoxiang Wang; Yue Wang; Xiaoqing Jiang; Bin Li (Cell Death and Disease)
Abstract Studies have shown that extracellular vesicles play a crucial role in maintaining homeostasis in healthy individuals and influencing disease pathology in patients. However, the mechanisms by which exosomes facilitate liver regeneration following portal vein ligation (PVL) remain unclear. Our previous research highlighted the critical role of the Notch signaling pathway in liver regeneration after PVL. Nevertheless, the involvement of liver-derived exosomes in actively promoting regeneration through the YAP-Notch signaling pathway and their role in cell proliferation have not been fully explored. In this study, we demonstrate that exosomes from hypertrophic liver tissue can activate the YAP-Notch signaling pathway both in vitro and in vivo, thereby promoting liver regeneration after PVL. Specifically, we show that these exosomes carry JAG1, which activates Notch signaling in recipient cells, a process that is inhibited by JAG1 antibodies. Co-immunoprecipitation and mass spectrometry (Co-IP-MS) identified JAG1 interactors, confirming that ALG-2 plays a critical role in linking SEC31A and Alix to facilitate the intracellular transport and sorting of JAG1 onto exosomes. Additionally, we reveal that YAP induces hepatocyte reprogramming into Sox9+ liver progenitor cells (LPCs) and promotes the release of JAG1+ exosomes via the SEC31A/ALG-2/Alix axis, thereby activating Notch signaling in neighboring cells and enhancing liver regeneration. These findings suggest that YAP+Sox9+ LPCs serve as a key source of JAG1+ exosomes, playing a vital role in liver regeneration following PVL.